An efficient strontium-based combustion inhibitor of ammonium perchlorate with a 2D-MOF structure. (6th June 2021) - Huang, Yao; Peng, Rufang; Jin, Bo
Abstract : A new strontium 2D-MOF was prepared and applied to the study of AP thermal decomposition. Abstract : In this study, a new strontium 2D-MOF, {[Sr(AFCA)2 (H2 O)2 ]·2H2 O} n (AFCA = 4-aminofurazan-3-carboxylic acid), was successfully prepared by slow evaporation at room temperature. Its structure was characterized by X-ray single-crystal diffractometry. DTA as an efficient thermal analysis method was used in this study to have a better understanding of the thermal decomposition of ammonium perchlorate (AP). The Kissinger and the Ozawa–Doyle methods were also applied to determine the apparent activation energy ( E ) and the pre-exponential factor ( A ) of AP thermal decomposition. After the addition of {[Sr(AFCA)2 (H2 O)2 ]·2H2 O} n in AP, there is an increase of 85.97 °C in the LTD stage of AP thermal decomposition and an insignificant decrease of 24.32 °C in the HTD stage. With the help of the TG–DSC–DTG method, we analyse the catalytic mechanism of AP in the LTD stage in detail. {[Sr(AFCA)2 (H2 O)2 ]·2H2 O} n can act as an efficient combustion inhibitor for AP thermal decomposition.